Correlation of woodfuel production participation among rural households in the drylands of Ethiopia - Girma, Gonche; Shimeles, Abebaw; Abate, Tensaye; Berhanu, Deginet; Alemayehu, Asabeneh; Belachew, Azmera (Frontiers in Forests and Global Change, 2024)
In general, wWoodfuel production and consumption has ve been a concern for multiple stakeholders in the arena of household energy use, deforestation and climate change issues. Research into the underlying decision process is growing but still insufficient. And sSuch a study offers opportunities to craft policies that enable diversifyingication of household energy consumption and livelihood options away from woodfuel use. Policymakers has lack ofan understanding onf factors correlated with households' participation in woodfuel production. This study, therefore, examined the correlation between household participation within woodfuel production and factors that influence households' participation in woodfuel production in dryland areas of Ethiopia. The data Data were collected from 1114 purposively selected woodfuelproducing and non-producing households through household surveys, key informant interviews and focus group discussions. The sampled households comprised included 775 participants and 339 non-participant households. The collected data were analyszed using descriptive statistics and a binary logistics regression model. The results revealed that drought and related shocks are the main factors that forced households to participated in woodfuel production. The model results revealed showed that age, education, landholding, livestock holding, production asset value, ownership of improved cook stoves ownership, number of years lived in the area, distance from the forest, access to forest extension and institutional membership are found to be statistically significant factors and negatively influencing household participation in woodfuel production. On the other wayhand, household expenditure and drought occurrence positively and significantly influence the participation of households in woodfuel production. The findings of the study suggest that ensuring sustainable dryland forest resource management and utilization of dryland forest resources requires due consideration of the socioeconomic, demographic, institutional and environmental factors correlated with the decision of householdshouseholds' decision to participate in woodfuel production through sound institutional setup and policy framework in the sector.